OPTIMASI WAKTU PRODUKSI ANTIBIOTIKA ISOLAT MIKROORGANISME DARI AIR LAUT BAJOE KABUPATEN BONE DENGAN VARIASI SUMBER NITROGEN - Rusli, Rusli; Fitriana, Fitriana (Jurnal Ilmiah As-Syifaa, 2011)
Optimization research has been done time on the production of antibiotics from bacterial isolate from Bajoe Distric Bone waters with nitrogen sources of variation, the first stage of the selection of isolates that have the greatest obstacle zone and which inhibits microbial isolates most of the isolates tested ERB 3 which inhibited Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa, Vibrio sp, Candida albicans and Aspergillus niger. Determination of the growth curve of the isolates with inoculate into a nutrient broth medium and incubated for 2 times 24 hours. Each interval of 2 hour was measured transmittance on spectrophotometer to determine the stationary phase. Results from growth curve obtained from the stationary phase at the 20th until the 48th hour. Determination of optimum fermentation conditions by varying the nitrogen source is peptone and tryptone. ERB 3 isolate was inoculated into the production medium and fermented using the medium of production in which every interval of 4 hours is making fermented products ranging from hour to hour-20thto48th. Activity was tested using agar diffusion method in the medium Glucose Nutrient Agar (GNA) against Staphylococcus aureus, Streptococcus mutans and Salmonella typhi. The results showed that the optimum time to produce antibiotics is the 24, 40 and 48hour and nitrogen source tryptone better than peptone.Â Keywords : Optimasi, Isolat, Antibiotika